Research on the application effect of arthroscopic access modification in meniscal injury repair - Shulin Li; Huayao Sun; Jiahao Zhang; Huiling Guo; Laipeng Yan; Faqiang Tang (Journal of Orthopaedic Surgery and Research)
Abstract Objective To investigate the application value of arthroscopic channel modification in meniscal injury repair. Methods We retrospectively analyzed the data of 100 patients with meniscus injuries treated with knee arthroscopy from December 2022 to December 2023 and divided them into a control group and a modified group according to the application of “arthroscopic access modification technology”. We compared the operation time, postoperative hospitalization time, VAS score, Lysholm knee function score, postoperative complications, and postoperative images of the patients in these two groups. We compared the operation time, postoperative hospitalization time, pre- and postoperative VAS scores, Lysholm knee function scores, postoperative complications and postoperative imaging indices of the patients in the two groups. Results All patients successfully underwent surgery and were followed up without intraoperative vascular or nerve injury or postoperative complications such as infection, wound necrosis or thrombosis. The average follow-up time was 16.03 ± 3.69 months; the average operation time and postoperative hospitalization time of the modified group were significantly better than those of the control group were (P < 0.05); the pain and knee function of the two groups significantly improved over time (P < 0.05); and, compared with those of the control group, the modified group could obtain a more satisfactory score at an early stage of the postoperative period (P < 0.05), and the comparison of the intermediate and long-term scores of the two groups was not statistically significant (P > 0.05). There was no statistically significant difference (P > 0.05). Conclusion The improved arthroscopic access technique can make the entry and exit of instruments into and out of the joint cavity smoother, improve the surgical field of view, significantly shorten the operation time, reduce the occurrence of intraoperative complications, improve the function of patients’ knee joints earlier, and increase their satisfaction with the operation.